2008
DOI: 10.3354/meps07217
|View full text |Cite
|
Sign up to set email alerts
|

Sources and sinks of larval settlement in Jasus edwardsii around New Zealand: Where do larvae come from and where do they go?

Abstract: Isolated adult populations tend to be interconnected via the larval stage. New Zealand red rock lobster Jasus edwardsii larvae metamorphose 12 to 24 mo after hatching. Because of this long larval life, J. edwardsii provides a useful species for studying population connectivity using satellite-derived ocean currents. In this study, tracks of J. edwardsii larvae originating from different populations are simulated to build a statistical picture of larval dispersal. By adding an algorithm for larval metamorphosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…By comparing our results with an earlier study by Chiswell and Booth (2008), we are able to determine whether the prevailing current regimes in the region are likely to be the predominant forces driving the population structure and also explore the significance to the levels of genetic differentiation we reported. Rock lobster connectivity patterns L Thomas and JJ Bell…”
Section: Consistency With Oceanographic Dispersal Models In New Zealandmentioning
confidence: 56%
See 4 more Smart Citations
“…By comparing our results with an earlier study by Chiswell and Booth (2008), we are able to determine whether the prevailing current regimes in the region are likely to be the predominant forces driving the population structure and also explore the significance to the levels of genetic differentiation we reported. Rock lobster connectivity patterns L Thomas and JJ Bell…”
Section: Consistency With Oceanographic Dispersal Models In New Zealandmentioning
confidence: 56%
“…The results from the model showed significant exchange among most regions, and the authors identified four major geographic areas associated with rock lobster larval dispersal around New Zealand: (1) the far north, (2) the east coast of the North Island, (3) the South Island and (4) the Chatham Islands. In addition to these four geographic regions, Chiswell and Booth (2008) identified high levels of local settlement at the bottom of the South Island and suggested that populations in this region are likely to be maintained by self-recruitment. Using a similar modeling approach, Chiswell et al (2003) investigated trans-Tasman dispersal rates and estimated that 9-14% of J. edwardsii larvae originating from the south east coast of Australia would be able to reach the west coast of New Zealand, which was used to explain the genetic homogeneity for J. edwardsii on the basis of mitochondrial DNA data (Ovenden et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations